Micronutrients concentration and content in corn as affected by nitrogen, phosphorus, and potassium fertilization - Ravinder Singh; Steven Sawatzky; Matthew Thomas; Samuel Akin; William R. Raun; Hailin Zhang; D. Brian Arnall (Agrosystems, Geosciences & Environment)
Abstract The interaction between nitrogen (N), phosphorus (P), and potassium (K) fertilizers significantly impacts the uptake of micronutrients in corn, influencing their availability in soil and uptake by plants. Understanding the interaction of macro‐ and micronutrients is a prerequisite to targeting nutrient balance in crop production. Therefore, a 2‐year field experiment was conducted to determine the effect of NPK fertilization on micronutrient uptake of rain‐fed corn (Zea mays L.). A randomized complete block design was employed with 12 treatments replicated three times. Different combinations of N, P, and K fertilizer rates were investigated for micronutrient concentration and uptake in rain‐fed corn. Findings revealed the order of nutrient accumulation in corn plants: iron (Fe) > manganese (Mn) > zinc (Zn) > copper (Cu). Nitrogen application influenced nutrient concentrations and uptake. Increasing N rates increased micronutrient concentrations in corn grain, except for Cu. Interestingly, Cu content in grains exhibited no correlation with nutrient supply, biomass, or other concentrations. As the N application rate increased, micronutrient content increased at early growth stage and physiological maturity. Phosphorus application showed negligible impact on grain micronutrient concentration and uptake. However, K application notably increased Mn, Fe, and Cu uptake in grains. This study underscores the need to consider not only grain yield but also nutritional quality when determining optimal NPK rates in rain‐fed corn cultivation.